COMPARISON ANALYSIS OF CORRELATIONS FOR INTERFACIAL FRICTION FACTOR APPLIED IN GAS-LIQUID ANNULAR FLOW IN VERTICAL PIPES - Paula Jr., C. F. de; Lima, L. E. M. (Revista de Engenharia Térmica, 2017)
Gas-liquid flows in pipes can occur in the form of an annular pattern in which the liquid flows as a thin film at pipe wall and the gas flows as a core in pipe center. This flow pattern is often encountered at boiling and condensation processes, for example, in industries of steam generation, cooling or petroleum. In annular flow, the interfacial friction factor is one of the important closing parameters for the definition of the interfacial shear stress and consequently the pressure gradient. In the literature, several correlations are found to estimate the interfacial friction factor. The main objective of this work is to carry out a comparative analysis of some these correlations against experimental data also obtained from the literature. The features and limitations of each correlation were observed, as well as the accuracy of each in relation to experimental data. The results obtained demonstrate that correlations analyzed, present relatively satisfactory results, despite the different characteristics of the correlations, however, it is necessary to carry out more extensive analyses involving others correlations and sets of experimental data.